"Nobody gave me information": Hospital experiences of Ghanaian families after maternal mortalitiesAJOG Global Reports at a Glance - LeAnn A. Louis, MD, MPH; Adu Appiah-Kubi, MBChB, FGCS; Ruth Owusu-Antwi, MBChB, MSc, FGCP; Thomas O. Konney, MD, FWACS, FGCS; Cheryl A. Moyer, PhD, MPH; Emma R. Lawrence, MD, MS (Elsevier, 2024)
Background: Rates of maternal mortality are highest in low-resource settings. Family members are often involved in the critical periods surrounding a maternal death, including transportation to health centers and financial and emotional support during hospital admissions. Maternal death has devastating impacts on surviving family members, which are often overlooked and understudied. Objective: Our study aimed to explore the hospital experiences of family members surrounding a maternal death, and to define their access to and need for institutional and psychosocial support. Study Design: This mixed methods cross-sectional study was conducted at an urban tertiary hospital in Ghana. Maternal mortalities from June 2019 to December 2020 were identified using death certificates. Participants, defined as husbands or other heads of households in families affected by maternal mortality, were purposively recruited. An interview guide was developed using grounded theory. In-person semi‐structured interviews were conducted in English or Twi to explore impacts of maternal mortality on family members, with a focus on hospital experiences. Surveys were administered on types of and needs for institutional support. Interviews were audio recorded, translated, transcribed, coded with an iteratively-developed codebook, and thematically analyzed. Survey data was descriptively analyzed. Results: Fifty-one participants included 26 husbands of the deceased woman, 5 parents, 12 siblings, and 8 second-degree relatives. Interviews revealed an overall negative hospital experience for surviving family members, who expressed substantial dissatisfaction and distress. Four themes regarding the hospital experience emerged from the interviews: 1) poor communication from healthcare workers and hospital personnel, which contributed to 2) limited understanding of the patient's clinical status, hospital course, and cause of death; 3) maternal death perceived as avoidable; and 4) maternal death perceived as unexpected and shocking. Survey data revealed that only 10% of participants were provided psychosocial support following the maternal death event, yet 93.3% of those who did not receive support desired this resource. Conclusion: The hospital experience was overall negative for family members and a lack of effective communication emerged as the root cause of this negative perception. Strategies to improve communication between healthcare providers and families are essential. In addition, there is an unmet need for formal mental health resources for families who experience a maternal death.